PENERAPAN PEMBELAJARAN Al-QUR’AN UNTUK MEMPERBAIKI BACAAN AL-QUR’AN PESERTA DIDIK (STUDI PADA TAMAN PENDIDIKAN AL-QUR’AN NURUL HUDA KARTOPURAN KECAMATAN SERENGAN SURAKARTA TAHUN AJARAN 2022/2023) - Fadhilah, Nurul; Rochmawan, Alfian Eko; Sulistyowati, S (MAMBA'UL 'ULUM, 2024)
TPQ is a non-formal Al-Qur'an education park where there are various lessons about the Al-Quran and how to improve reading and tahsin so that TPQ students are introduced to what the Al-Qur'an is and also about learning Islamic religious education. That way students will know how good morals are according to the teachings of Rasulullah SAW. This TPQ study aims to find out the application of Al-Qur'an learning, and to find out the factors that support and hinder the application of quality Al-Qur'an learning at TPQ Nurul Huda Kartopuran, Serengan District, Surakarta, Academic Year 2022/2023. This study uses qualitative methods and uses data collection tools in the form of observation, interview methods, and documentation. Then from the results obtained, the researcher will describe briefly and then the researcher will conclude so that the results are appropriate. Based on the results of the research that has been obtained, the application of learning the Koran at TPQ Nurul Huda Kartopuran, Serengan District, Surakarta, for the 2022/2023 academic year is quite good, because there are competent teachers who are educated first so that learning can develop. In addition, the application of learning is also assisted by the existence of guidelines and several methods that have been used. The factors that support and hinder the application of Al-Qur’an learning at TPQ Nurul Huda Kartopuran, Serengan District, Surakarta, for the 2022/2023 Academic Year are, collaboration between TPQ administrators and parents, facilities and infrastructure, donors, and competent teachers.